Exploring Youth Livelihood Challenges in Post-Conflict Northern Uganda - Kitambo, Enos; Omona, Julius; Mugumya, Firminus (ARJESS, 2020)
The persistence of youth challenges is a global concern, with unemployment biting the generation. In Uganda, the youth comprise the highest population (UBOS, 2014). The young ones are battling socio-economic challenges despite, natural resource availability, programmes from government, and NGOs. This study is questioning the continued misery of the youth in post conflict northern Uganda yet the country is endowed with natural resources and entrepreneurial interventions. The major objective of the study is to examine challenges facing youth and suggest best entrepreneurship measures to youth empowerment. The study employed explorative methods design to generate both qualitative data with a descriptive survey. The youth (18-30 years) as the primary respondents were randomly sampled. The findings portray that youth unemployment and poverty originated from the Lord’s Resistance Army (LRA) war which lasted for over 20 years and implanted dependence syndrome, laziness and negative attitudes towards agriculture and work. Limited entrepreneurial training, politicisation of livelihood programmes, inadequate capital and communal land, communication deficiencies were reported to be constraining factors to youth livelihood. The study therefore recommends youth entrepreneurship through intensive training, sensitisation, and parental inclusion in planning and implementation, access to market information and behavioural change for enhancing individual functioning.
Keywords: Livelihood challenges; entrepreneurial interventions